The European Investment Bank: Lessons for developing countries - Stephany Griffith-Jones; Judith Tyson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The paper considers the experience of the European Investment Bank and addresses policy lessons for developing countries as they seek finance for development. The paper argues that the key lesson for developing countries is that the traditional role of a development bank in closing market gaps in long-term, low-cost and stable infrastructure lending and in anticyclical financing remains relevant for developing countries but needs to be directed towards new goals. The paper also proposes that an optimal structure is a regionally owned development bank, as this would allow critical advantages of regional ownership, control and responsiveness.
Keywords: E59; F36; F59; G18; 330; development banks; European Investment Bank; infrastructure financing; development financing; environment; Entwicklungsbank; Entwicklungsfinanzierung; Infrastrukturinvestition; Entwicklungsländer